Hubungan Pengetahuan Ibu Tentang ASI Eksklusif dengan Pemberian ASI Eksklusif pada Bayi - Ina Kuswanti; Jenny Marcelina Faot (LPPM STIKES Guna Bangsa, 2017)
Background: The giving of exclusive mother’s milk was recommended for the baby until aged 6 months, because the mother’s milk contained a full nutrients to grow and development for the baby. The successful in giving exclusive mother’s milk was influenced by the mother’s knowledge about the exclusive mother’s milk. The data obtained also shownd that Danurejan 1 public healt was the lowest in exclusive breastfeeding gift that is 12,31%. Results of interviews with mothers of babies 6-12 months found mother’s who did not breastfeed exclusive of 7 people. Objective: To know the correlation of knowledge level of mother about exclusive mother’s milk with the deliverance of exclusive mother’s milk for the baby. Method: This research used an analytic survey method with a cross sectional approach. The research population was 132 people, the research sample was 57 people taking with a purposive sampling method. The research instrument was a close questionnaire with Gutman Scale. The data analysis method used a frequency distribution and chi square correlation. Result: The most mothers has a knowledge about exclusive mother’s milk in a good categorized (50%) and the most mothers gave the mother’s milk exclusively (82,5%). There were a significant correlation between mother’s knowledge and exclusive mother’s milk with the deliverance of exclusive mother’s milk for the baby with p count = 37,817 with sig 0.000 < 0,05. Conclusion: There were a significant correlation between the mother’s knowledge about exclusive mother’s milk with the deliverance of exclusive mother’s milk.